2013
DOI: 10.1038/ejhg.2013.192
|View full text |Cite
|
Sign up to set email alerts
|

Deletions involving genes WHSC1 and LETM1 may be necessary, but are not sufficient to cause Wolf–Hirschhorn Syndrome

Abstract: Wolf-Hirschhorn syndrome (WHS) is a complex genetic disorder caused by the loss of genomic material from the short arm of chromosome 4. Genotype-phenotype correlation studies indicated that the loss of genes within 4p16.3 is necessary for expression of the core features of the phenotype. Within this region, haploinsufficiency of the genes WHSC1 and LETM1 is thought to be a major contributor to the pathogenesis of WHS. We present clinical findings for three patients with relatively small (o400 kb) de novo inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 49 publications
2
36
0
5
Order By: Relevance
“…NSD1 and NSD2 have each been linked to human developmental overgrowth syndromes. The NSD2 gene is among a group of genes deleted in Wolf-Hirschhorn syndrome, and loss of NSD2 is thought to be responsible for a subset of the clinical features characteristic of this syndrome (Andersen et al 2014). Deletion or loss-of-function mutations involving NSD1 results in Sotos syndrome, an autosomal dominant overgrowth syndrome characterized by a distinctive facial appearance, delayed development, and learning disabilities (Douglas et al 2003;Turkmen et al 2003).…”
Section: The Nuclear Receptor-binding Set Domain (Nsd) Family Of H3k3mentioning
confidence: 99%
“…NSD1 and NSD2 have each been linked to human developmental overgrowth syndromes. The NSD2 gene is among a group of genes deleted in Wolf-Hirschhorn syndrome, and loss of NSD2 is thought to be responsible for a subset of the clinical features characteristic of this syndrome (Andersen et al 2014). Deletion or loss-of-function mutations involving NSD1 results in Sotos syndrome, an autosomal dominant overgrowth syndrome characterized by a distinctive facial appearance, delayed development, and learning disabilities (Douglas et al 2003;Turkmen et al 2003).…”
Section: The Nuclear Receptor-binding Set Domain (Nsd) Family Of H3k3mentioning
confidence: 99%
“…Сьогодні рекомендують таких фахівців, які по-винні спостерігати дитину: клінічний генетик, пе-діатр, невролог, кардіолог, офтальмолог, ортопед, логопед, отоларинголог, уролог [1,4].…”
Section: îñíîâí³ ñèìïòîìè òà ïðîÿâè ïðè ñèíäðîì³ âîëüôà -õ³ðøõîðíàunclassified
“…1,2 , Ìàöþðà Î.È. 1,2 , Áóëàê Ã.Â. 1 Îïûò äèàãíîñòèêè è íàáëþäåíèÿ ðåáåíêà ñ ñèíäðîìîì Âîëüôà -Õèðøõîðíà Резюме.…”
Section: отримано 19012017unclassified
See 1 more Smart Citation
“…Among the candidate genes already described for WHS, these authors considered LETM1 likely to be pathogenetically involved in seizures. Andersen et al [2014] suggested that hemizygosity of WHSC1 and LETM1 could be a major contributor to the pathogenesis of WHS. However, not all patients with deletions overlapping both WHSC1 and LETM1 express the full WHS phenotype, and deletions elsewhere in 4p16.3 have been identified in patients with features overlapping WHS.…”
mentioning
confidence: 99%